Premenstrual Syndrome in Reproductive Age Females in Muzaffarabad AJK - Ghos, Attia Ghulam; Ghos, Aymen Ghulam (Indus Journal of Bioscience Research, 2025)
Objective: To determine the frequency and symptoms of premenstrual syndrome among reproductive aged women in Muzaffarabad AJK. Study Design: Cross sectional study. Duration and Place of Study: This research was conducted from 10th January 2025 to 10th June 2025 at the Obstetrics and Gynecology Department of AIMS Hospital Muzaffarabad AJK. Methodology: A total of 356 participants, aged 18–45 years, were selected. The Premenstrual Symptoms Screening Tool was adapted as a tool for screening symptoms of PMS, which comprise psychiatric symptoms such as mood changes, irritability, anxiety, depression, and fatigue, as well as somatic symptoms such as back ache, bloating, headaches, breast tender point, as well as abdominal discomfort. Continuous variables were presented in mean value with standard deviation as well as nominal variables which were presented as the form of frequency percent, as comparisons were conducted through the chi-squared test. Results: The prevalence of Premenstrual syndrome in the study group was found to be 46.10% (n=164). Anxiety as a psychological symptom was found in 70.70% (n=116) of the population, and as a somatic symptom, bloating was found in 61.00% (n=100) of the population. There was no association found between the variables of age, body mass index, marital status, or use of contraceptives with the prevalence of PMS (p > 0.05). Conclusion: The study indicates that PMS is a common condition affecting nearly half of reproductive-aged women.